Rukyatul Hilal and Hisab: A Comparative Study of Muhammadiyah and Nahdlatul Ulama in Determining the Beginning of the Hijri Month - Rivaldi, Muhammad Arma; Isnaeni, Ahmad; Masruchin, Masruchin (Mauriduna : Journal of Islamic Studies, 2026)
Determining the beginning of the Hijri months often gives rise to differences of opinion, especially between Islamic organizations Muhammadiyah and Nahdlatul Ulama (NU). These differences stem from the different method used for hisab (astronomical calculation) and rukyat (moon sighting), as well as the interpretation of Quranic verses. This study aims to analyze the interpretation of Quranic verses concerning the crescent moon and hisab to compare the perspectives of Muhammadiyah and NU. This study uses a qualitative approach with the thematic interpretation method of Quranic verses related to the crescent moon and reckoning. Data were obtained from primary sources such as the Koran and tafsir books, as well as secondary sources such as books and journals.The data were then analyzed comparatively to identify differences between the two groups. The results show that Muhammadiyah prioritizes hisab based on rational interpretation of Quranic verses, while NU prioritizes rukyat with a textual approach based on texts and hadith. These differences have practical implications for determining the beginning of hijri, which are often inconsistent. Different understandings of verses about the crescent moon and hisab reflect the epistemological characteristics of each mass organization. Despite their differing approaches, both aim to safeguard the validity of sharia and the unity of the Muslim community.